PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DAN ANAK-ANAK YANG MENJADI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL (Studi Terhadap UU No. 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual) - Shapira, Kania; Anggraeni, Siti Wulan; Rossa, Reva Della; Chairunnisa, Chairunnisa; Fauziah, Alfiah Farhah; Febrianty, Yenny (Jurnal Pahlawan, 2023)
The passing of Law No. 12 of 2022 on the Crime of Sexual Violence on May 9, 2022, became an umbrella of positive legal protection against sexual violence experienced by women and children as the majority of victims of sexual violence. The Ministry of Women's Protection and Child Protection noted that as many as 25,050 women were victims of sexual violence in 2022. The birth of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence is a perfection of previous laws and regulations with the same substance so as to protect and guarantee the rights of victims of sexual violence. This study aims to determine the effectiveness of the implementation of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence in tackling cases of sexual violence crimes, especially against women and children. The method used in this research is normative-empirical law by including secondary data from literature studies and primary data obtained directly from the general public through questionnaires. The conclusion obtained is that Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence has not been implemented effectively because there are still many cases that experience obstacles to justice. Keywords: Children, Crime, Sexual Violence, Women